History “through the looking glass” (Historia, 2021)
This article deliberates on the South African Department of Basic Education’s announcement in February 2018 to implement history as a compulsory school subject to the final year of secondary schooling. It outlines the process undertaken by the History Ministerial Task Team and assesses the report it issued, along with the initial reaction to its intent. It reflects on the chequered past of the position and place of history within the South African education system, re-visiting some of the post-democracy debates that have perpetuated from the previous century and spilled over into the present. In the paradigm of Alice through the Looking Glass, it suggests that we might need to go “backward before going forward” in order to stop repeating this conundrum.
Keywords: school history; history curriculum; Department of Basic Education; compulsory subject; national education; post-apartheid education